Showcasing The Uniqueness Of A Marine Destination By Adopting Local Wisdom - Nurdina Prasetyo (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Development based on local wisdom and indigenous practices can be particularly effective since local wisdom is often the only asset the local people control, and certainly one with which they are very familiar. Yet, literature on marine tourism development shows a scarcity of studies that draw from local wisdom, even though local community participation is underlined as one of the most important factors in successful marine tourism development. This paper explores the role of adopting local wisdom and indigenous practices in marine tourism development in showcasing the uniqueness of marine tourism destinations, with the case study of Misool, Raja Ampat, Indonesia. Misool is one of the islands in Raja Ampat which attracts marine tourists from around the world due to its abundance marine life. Using a conversational method for data collection, this paper analyzes how the integration of local wisdom and indigenous practices in tourism takes place and how tourists appreciate them. Findings from conversations with local people who worked as tour guides and dive guides show that the guests expressed appreciation when being asked to follow specific things according to their local wisdom and indigenous practices when visiting some of the tourist attractions or dive sites. Some of their guests stated that Misool is unique because of these practices. These findings reveal that adopting local wisdom and indigenous practices in a marine tourism destination emphasizes the uniqueness of the place. Moreover, the unique culture of the local community can also be an added value to the total tourism experience.